(3GdebGeGJs - (3GdMQjQj GdHUQj, CHh eMeO, GdbGSe Hf Ydj Hf eMeO Hf YKeGf, (B516 (3g`s ((3GdMSjf Hf fGUQ Hf YHO GdMajXs)
(3ChdgG (B:s
(3Gddge EfG fMeO Ydi eG YdeJ ef GdHjGf hCdgeJ ef GdJHjGfs
(3BNQgG (B:s
(3hGSJQTOg Edi eG jYUe ef GdSgh hjMXi HGdYah Efg Cgd GdJbhi hCgd GdeZaQI hhdj GdNjQGJ aj GdOfjG hGdBNQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 5 / 177s
(3eYLe GdeDdajf(B: 2 / 645s
(3cTa GdXfhf(B: 2 / 1782s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdCOHs